Last call for RHIC predictions - Bass, Steffen A.; Stachel, Johanna (Arxiv, 1999)
This paper contains the individual contributions of all speakers of the session on 'Last Call for RHIC Predictions' at Quark Matter 99, and a summary by the convenor.
Gesehen am 27.02.2020